Pulmonary sarcomatoid carcinoma: a case report - Shen, Xiao-yong; Lin, Zhi-feng; Lin, Qiang; Ruan, Zhen; Huang, Hai-long; Ju, Chao-qiang; Wang, Jin (Contemporary Oncology/Współczesna Onkologia, 2013)
Sarcomatoid carcinoma (SC) is a rare primary malignant tumor in which both carcinomatous and sarcomatous elements occur. It can occur in many different organs and anatomical locations, such as the skin, thyroid gland, bone, urinary tract, breast, pancreas, liver and other areas. Of them, pulmonary sarcomatoid carcinoma (PSC) is a rare malignant cancer composed of sarcoma and sarcoma-like tumors with spindle or giant cell features. Here a case of a 75-year-old Chinese man with a six-month history of cough and hemoptysis is reported. Chest X-ray showed a tumor shadow in the left lung field. Chest computed tomography (CT) scan showed a lobulated mass in his left hilum and even the left pulmonary artery. Pleomorphic interstitial cells were found by bronchoscopic brushing. To establish a definitive diagnosis for PSC, a left pneumonectomy was performed. The pathological stage was IIB (pT2N1M0) based on the tumor node metastasis (TNM) staging system. The tumor’s pathology, histology, immunohistochemistry and treatment methods are discussed.